47.8k views
4 votes
Pls answer
. its urgent pls
an

Pls answer . its urgent pls an-example-1

2 Answers

5 votes

Answer:

option c

Explanation:


(-4)/(3) * y = (-3)/(4)

shift -4/3 to the right hand side . when it shifts to other side miltiplication changes to division

y =
(-3)/(4) /(-4)/(3)

now do reciprocal

y =
(-3)/(4) *(3)/(-4)

y =
(-9)/(-16)

minus and minus gets cancel

y =
(9)/(16)

y =
((3)^2)/((4)^2)

y =
((3)/(4))^2

User Ilyssa
by
6.3k points
4 votes

Answer:

a

Explanation:

User MikeyWard
by
6.5k points